On an integral of equation of Voltaire with delta-type kernel - Akhmanova, D.M.; Omirbekova, A.Ye. (Bulletin of the Karaganda University. Mathematics Series, 2015)
The article considers the singular integral equation Volterra of the second kind, which reduces number of boundary value problems for the heat equation loaded. In view of unbounded intervals of integration and delta kernel does not apply to it the method of successive approximations. Construct the corresponding characteristic equation, the solution of which is found in explicit form. For the original equation, the method of equivalent regularization, found its spectrum.